ANALISIS SIKAP VARIASI BAHASA MEDAN FORMAL DAN NONFORMAL MASYARAKAT MEDAN PERJUANGAN - Lesteria Sagala; Nopri Sitohang; Jeslina Batubara; Anggilina Sirait; Elza Leyli Lisnora Br Saragih (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze attitudes toward formal and informal language variation used by the Medan Perjuangan community from a sociolinguistic perspective. Language is viewed as a social phenomenon influenced by social factors such as age, social status, cultural background, and communicative situations. The research data consist of dialogues representing social interactions within the Medan community and are analyzed using a qualitative descriptive approach. The analysis focuses on speakers’ and listeners’ social identities, social settings of speech events, social evaluations of utterances, and levels of language variation. The findings indicate that the Medan dialect and informal language varieties dominate interactions in informal contexts, while more neutral and functional varieties are used in public service contexts. These language variations reflect speakers’ social identities, social relationships, and local cultural norms. Therefore, language variation functions not only as a means of communication but also as a marker of social and cultural identity within the Medan Perjuangan community.